Arid Horticulture: An Overview (Indian Journal of Arid Horticulture, 2025)
The arid region is spread over 38.7 million hectares, mainly in the states of Rajasthan, Gujarat, Haryana, Punjab, and Andhra Pradesh. The area is marked by extreme climatic conditions, making the cultivation of traditional crops non-economical. In such a situation, arid horticulture offers ample scope to develop these regions. The present communication attempts to provide an overview of the technologies developed that can be used to transform the arid ecosystem into a horticultural hub, ensuring income generation and nutritional security for the inhabitants.
Keywords: Arid region; horticulture; orchard management